Police legitimacy, ideology and qualitative methods: A critique of procedural justice theory. (November 2015) - Harkin, Diarmaid
I argue that there are unconsidered complexities to police legitimacy and use examples from my study of police–public consultation forums in Edinburgh, Scotland to illustrate. I make a number of conceptual and methodological critiques by drawing upon Steven Lukes' social theory on power to show how legitimacy can be a product of authority relations as much as it is a cause of authority relations. This view finds support from systems-justification theory. I also tackle Beetham's conception of legitimacy and argue that there is evidence from police studies that the police breach his key antecedents to legitimacy without incurring the expected consequences. Furthermore, I take an original methodological approach to studying police legitimacy which reveals additional insights. For instance, Bottoms and Tankebe suggest legitimacy addresses multiple 'audiences'; I would also add that it addresses multiple recipients as legitimacy is shown to vary among officers and positions of rank.